Bibliometric analysis of preoperative radiotherapy for locally advanced rectal cancer: evolution and future - Weng, Zhen-Hong; Hu, Hao-Kai; Zhou, Zi-Shan; Huang, Li-Sheng; Chen, Bin-Bin; Lin, Jia-Rui (Frontiers in Medicine, 2025)
BackgroundPreoperative radiotherapy of rectal cancer has been a hot topic of research in recent years with the introduction of total neoadjuvant therapies and immunotherapeutic agents. We utilized bibliometrics and visualization analysis to examine studies in this field, aiming to identify current hotspots and research trends.MethodWe searched the Web of Science database for all publications related to preoperative radiotherapy of rectal cancer in the past 10 years. Using bibliometric analysis software, such as VOSviewer, CiteSpace and R-studio, we extracted and analyzed the data, summarizing the publication output of countries, institutions, authors, and journals in this field, and analyzing their relationships. We also summarized the keywords, burst words, and most cited articles, and analyzed the relationships among them.ResultsWe found 794 publications in the field, sourced from 217 journals or books, involving 5,805 authors from various organizations and countries. Through bibliometric analysis, we observed a growing trend in the number of publications in preoperative radiotherapy of rectal cancer over the past 10 years. China, United States and Italy were the top countries in terms of publication output. Sun Yat-sen University, Fujian University, and Fudan University were the top three medical centers in terms of publication output, while Leiden University from Netherlands led globally in terms of citation impact. Professor Zhen Zhang, Sanjun Cai, and Ji Zhu were the top three authors with the highest publication output. The most highly cited journals in this field includes “The Lancet Oncology,” “J Clinical Oncology,” and “Annals of Oncology.” Journals such as “Radiotherapy and Oncology,” “Frontiers in Oncology,” and “BMC Cancer” have the highest number of articles published. Based on the analysis of keywords and burst words, we found that “preoperative chemoradiation” and “oral capecitabine” were the research hotspots before 2016, while the focus shifted to “short-course radiotherapy” and “long-term outcomes” after 2017. Currently, the most frequently cited publications mainly summarize multicenter clinical studies and total neoadjuvant treatment models and immunotherapy.ConclusionResearch on preoperative radiotherapy of rectal cancer is increasing year by year, and attracting attention from high-cited journals such as “The Lancet Oncology,” “JCO,” and “Annals of Oncology.” Based on current data, the total neoadjuvant treatment models and radiation combined with immunotherapy are the research trends.